6-2(x-3)+4=4(2-3x)

Simple and best practice solution for 6-2(x-3)+4=4(2-3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-2(x-3)+4=4(2-3x) equation:


Simplifying
6 + -2(x + -3) + 4 = 4(2 + -3x)

Reorder the terms:
6 + -2(-3 + x) + 4 = 4(2 + -3x)
6 + (-3 * -2 + x * -2) + 4 = 4(2 + -3x)
6 + (6 + -2x) + 4 = 4(2 + -3x)

Reorder the terms:
6 + 6 + 4 + -2x = 4(2 + -3x)

Combine like terms: 6 + 6 = 12
12 + 4 + -2x = 4(2 + -3x)

Combine like terms: 12 + 4 = 16
16 + -2x = 4(2 + -3x)
16 + -2x = (2 * 4 + -3x * 4)
16 + -2x = (8 + -12x)

Solving
16 + -2x = 8 + -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
16 + -2x + 12x = 8 + -12x + 12x

Combine like terms: -2x + 12x = 10x
16 + 10x = 8 + -12x + 12x

Combine like terms: -12x + 12x = 0
16 + 10x = 8 + 0
16 + 10x = 8

Add '-16' to each side of the equation.
16 + -16 + 10x = 8 + -16

Combine like terms: 16 + -16 = 0
0 + 10x = 8 + -16
10x = 8 + -16

Combine like terms: 8 + -16 = -8
10x = -8

Divide each side by '10'.
x = -0.8

Simplifying
x = -0.8

See similar equations:

| 12=-2-4 | | 7y+6x=6 | | -9a+45=-18 | | 3xsquared-24x+45=0 | | 16=-8c+9c | | (9x+2)(9x-1)=9x^2+3x-2 | | Y=0(-3)+-4 | | 5(5x-6)=67.5 | | 3x^2+15x+30= | | 8(n+1)-1=3(8+3n)-3 | | -x-13=-31 | | -6=3u4+12 | | y=4(-3)+3 | | 3x^2+15x+25= | | -6x^2-20x+16=0 | | (9x+2)(9x-1)=x | | 3x-17=x-1 | | 16x^4-64=0 | | 2x+11=43-3x | | 15-2(4)= | | 4n+12=4n+12 | | h+11.3=-11.3 | | 15-2(2)= | | 3x-5=72 | | a(n+1)= | | h=-8t^2+63 | | F(x)=62+35log(11-4) | | 12x+3=32 | | -6+2(10)= | | 0.6x-14=0.4x | | f(x)=9x^2+3x-2 | | 9x+3y-36=0 |

Equations solver categories